Peran Celebrity Endorser, Social Media Marketing dan Gaya Hidup terhadap Impulse Buying: Studi pada Pengguna Body Lotion Scarlet Whitening - Dina, Siva Bella; Marlien, R. A. (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to determine the effect of celebrity endorser, social media marketing, and lifestyle on impulsive buying behavior Scarlett Whitening body lotion product. By using a purposive sampling technique, 102 respondents were obtained by a Google form questionnaire which was distributed via social media. The resulting data were processed and analyzed using multiple linear regression analysis methods, by using the classical hypothesis test to examine the accuracy of the model and the t-test and coefficient of determination (R2) test to analyze the hypothesis. The results prove that celebrity endorsers and lifestyle have a positive and significant effect on impulse buying. On the other hand, social media marketing has proven to have no effect on impulse buying. Keywords: Celebrity Endorser, Social Media Marketing, lifestyle, and Impulse Buying